Ayat Al-Quran Tentang Alam Takambang Jadi Guru dalam Lukisan Kaligrafi - Rizki Hamdani (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Indonesia is known for its rich ethnic and cultural diversity, one of which is the Minangkabau ethnic group, renowned for its strong ancestral traditions. This research aims to visualize the philosophy of